Synthesis and antiproliferative activity of pyrrolo[3,2-b]pyridine derivatives against melanoma - Kim, Hee Jin; Jung, Myung-Ho; Kim, Hwan; El-Gamal, Mohammed I.; Sim, Tae Bo; Lee, So Ha; Hong, Jun Hee; Hah, Jung-Mi; Cho, Jung-Hyuck; Choi, Jung Hoon; Yoo, Kyung Ho; Oh, Chang-Hyun (Pergamon Press Ltd., 2010)
Synthesis of a new series of diarylureas and amides having pyrrolo[3,2-b]pyridine scaffold is described. Their in vitro antiproliferative activity against human melanoma cell line A375 and HS 27 human fibroblast cell line was tested and the effect of substituents on the pyrrolo[3,2-b]pyridine was investigated. The newly synthesized compounds, except meta-substituted derivatives (Ij-k and Iv-w), generally showed superior or similar activity against A375 to Sorafenib. Among all of these derivatives, compounds Ir and It having 5-benzylamide substituted 4'-amide moieties showed the most potent antiproliferative activity against A375. (C) 2009 Published by Elsevier Ltd.
Keywords: REFRACTORY SOLID TUMORS; FACTOR RECEPTOR INHIBITOR; RAF KINASE; SUBSTITUTED UREAS; PHASE-I; BAY-43-9006; THERAPY; PHARMACOKINETICS; INTERLEUKIN-2; PATHWAY